Profil Kemampuan VO2Max Atlet Tinju Kabupaten Sukoharjo - Damai Mahendra, Muhammad; Fatoni, Muhad; Jariono, Gatot; Nurhidayat, Nurhidayat (Universitas Hamzanwadi, 2024)
This study aims to assess the level of vo2max of male and female boxing athletes using the bleep test and analyze differences in results based on gender. The research method used a descriptive design with a cross-sectional approach, involving 17 male boxing athletes and 5 female boxing athletes as samples. The results showed that the maximum vo2max of male athletes was 57.1 ml/kg/minute, with a minimum value of 29.2 ml/kg/minute and an average of 45.7 ml/kg/minute, in the “good” category. The frequency distribution of male athletes was 11.8% in the “excellent” category, 17.6% in the “very good” category, 29.4% in the “good” category, and 29.4% in the “fair/medium” category. There were no athletes in the “deficient” or “very deficient” categories. Meanwhile, the maximum vo2max of female athletes was 53.5 ml/kg/min and the minimum was 32.5 ml/kg/min, with an average of 41.6 ml/kg/min, categorized as “very good”. The frequency distribution of female athletes showed 40% in the “excellent” category, 20% in the “very good” category, 20% in the “good” category, and 20% in the “fair/medium” category. There were no female athletes in the “deficient” or “very deficient” categories. In conclusion, female boxing athletes generally have a higher vo2max than male athletes. These findings suggest the need for adjustments to training programs to improve the vo2max of athletes who are in the “fair/moderate” and “very poor” categories.